Celiac Disease: Correlation of Clinical Presentation, Endoscopic Findings with Tissue Transglutaminase IgA Level - Sana Zulfiqar, Aneela Qureshi, Amin Fahim, Sadia Adnan, Sumreen Kashif, Shomail Saeed Siddiqui, Muhammad Sadik Memon, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: To observe the various clinical presentations and endoscopic findings in patients with Ceiliac disease (CD) and its correlation with the tissue transglutaminase IgA level. Study Design: Cross sectional, observational study. Place and Duration: Department of Pathology, Isra University Hospital Hyderabad, from July 2013 to December 2013. Material & Methods: Endoscopy was carried out in 96 patients after taking base line investigations and during endoscopy the naked eye examination was done to see any abnormality. The clinical presentation was noted as per proforma. Results: The result shows that, commonly CD patients presented with gastrointestinal symptoms seen in 64 (66.7%) cases, whereas 26 (27.1%) presented with Non gastrointestinal symptoms of CD and 6 (6.2%) with asymptomatic (silent) disease. Out of 96 cases, 42 (43.8%) cases had decreased and flat intestinal folds in CD patients and mean ± S.D of tTGA level was 55.08±35.71 U/ml; whereas decreased and serrated folds in 36 (37.5%) of cases, nodularity of mucosa in 2 (2.1%) of cases, marbal appearance in 5 (5.2%) , normal appearance of mucosa in 3 (3.1%) and edematous mucosa in 2 (2.1%) of cases. Conclusion: Patients with CD commonly presents with clinical gastrointestinal symptoms with decreased and flat folds on endoscopy. However there was non significant correlation among serum tissue transglutaminase IgA level, clinical presentation and endoscopic findings.